Tigecycline Therapy for Infections Caused by Extended-Spectrum β-Lactamase-Producing Enterobacteriaceae in Critically Ill Patients - Wen-Liang Yu; Nan-Yao Lee; Jann-Tay Wang; Wen-Chien Ko; Chung-Han Ho; Yin-Ching Chuang (MDPI AG, 2020)
We aimed to evaluate tigecycline on the clinical effectiveness in treating complicated skin and soft tissue infections (cSSTI), complicated intra-abdominal infections (cIAI), and pneumonia, caused by extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae, as data are limited. From three medical centers in Taiwan, we retrospectively studied the cSSTI, cIAI, and/or pneumonia caused by ESBL-producing Enterobacteriaceae. Among the 71 patients, including 39 patients infected with Klebsiella pneumoniae, 30 infected with Escherichia coli and others, the clinical success rate of tigecycline-based therapy was 80-90% for pneumonia and cSSTI caused by E. coli and 50-60% for cIAI caused by K. pneumoniae and E. coli. Microbiological and clinical outcome of pneumonia caused by carbapenem-resistant K. pneumoniae was poor. Univariate Cox analysis showed that dyspnea, SOFA score, septic shock, thrombocytopenia, prolonged prothrombin time, and lesser microbiological eradication were significant factors associated with 30-day mortality after the end of therapy. Cox regression proportional hazards model revealed dyspnea and a SOFA score > 8 to be independently associated with time to death. For ESBL producers, tigecycline showed good effects for cSSTI and pneumonia by E. coli, ordinary for cIAI, but ineffective for pneumonia by K. pneumoniae. Dyspnea and a high SOFA score predict a poor outcome.